Restorative Justice dalam KUHAP Baru: Antara Kepastian Hukum dan Diskresi Aparat Penegak Hukum - Muh Hajoran Pulungan; Mosgan Situmorang (Law Policy Strategy Agency, Ministry of Law of The Republic of Indonesia, 2026)
The restorative justice provisions in the New Criminal Procedure Code mark a paradigm shift in the Indonesian criminal justice system from a retributive approach to a more humanistic and recovery-oriented approach. This study aims to analyze the construction of restorative justice provisions in the New KUHAP and assess their implications for the principle of legal certainty and the limits of the authority of law enforcement officers. The research method used is normative legal research with a statutory and conceptual approach, through an examination of the principles of legality, legal certainty, and the theory of discretion in criminal law. The results show that although restorative justice provides flexibility in case resolution and has the potential to deliver substantive justice, its provisions, which have not been formulated in a limited and measurable manner, have the potential to create disparities in implementation and open up room for abuse of authority. Therefore, the formulation of more stringent norms regarding case boundaries, procedures, and oversight mechanisms is needed to ensure that the application of restorative justice remains within the corridor of the principles of legality and the principle of equality before the law.